The role of comprehensive geriatric assessment in the identification of different nutritional status in geriatric patients: a real-world, cross-sectional study - Ju, Yanmin; Lin, Xiaoye; Zhang, Kexin; Yang, Di; Cao, Mengyu; Jin, Huijing; Leng, Jiyan (Frontiers in Nutrition, 2024)
Background: Malnutrition is an often unrecognized problem, but it is common in older patients and leads to adverse outcomes.The purpose of this study is to analyze the prevalence of the risk of undernutrition in elderly patients and the correlation between CGA and nutritional status, and to determine the nutritional status of elderly patients.Methods: This is a real-world cross-sectional study of continuously enrolled elderly patients aged 65 years or older with a complete CGA database. CGA inventory was prepared by compiling and screening general information, body composition and blood biochemical results. MNA was also conducted for each elderly patient to screen for malnutrition. A multivariable logistic regression analysis was used to determine the association between the CGA and nutritional assessment.The average age of the 211 selected elderly patients (160 men and 51 women) was 79.60 ± 9.24 years, and their ages ranged from 65 to 96 years. After controlling for confounders, patients with a history of PUD (OR=2.353, P=0.044), increased ADLs & IADLs scores (OR=1.051, P=0.042) or GDS scores (OR=6.078, P<0.001) may increase the incidence of the risk of undernutrition respectively, while an increase in BMI (OR=0.858, P=0.032) may lower the incidence of malnutrition risk.In addition, increased ADLs & IADLs scores (OR=1.096, P=0.002) or GDS scores (OR=11.228, P<0.001) may increase the incidence of undernutrition. However, increased MMSE (OR=0.705, P<0.001), BMI (OR=0.762, P=0.034), UAC (OR=0.765, P=0.048) and CC (OR=0.721, P=0.003) may decrease the incidence of undernutrition, respectively.The study found that the prevalence of risk of undernutrition in elderly patients was the highest. Risk of undernutrition was independently associated with peptic ulcer disease, ADLs & IADLs, GDS and BMI. However, we found that when the nutritional status reached the level of undernutrition, it was related to more factors, including ADLs & IADLs, MMSE, GDS, BMI, UAC and CC. Determining the level of malnutrition through CGA may help to prevent and intervene malnutrition as early as possible.